Marcus Meibomius and his Manuscripts. (18th June 2019) - Lintott, Rosalind
Abstract: This essay considers the collections of books and manuscripts belonging to the antiquary and librarian Marcus Meibomius (1621–1710) through records relating to three separate auctions of these volumes. Using Johann Heinrich May's 1720 catalogue of Zacharias Conrad von Uffenbach's manuscripts, it reconstructs aspects of the 1711 posthumous sale of Meibomius's library. It examines in particular Meibomius's interaction with one of his Latin manuscripts, now in Wolfenbüttel, providing new evidence for part of his stay in England in the 1670s, and for the early-modern circulation of the text of the Defloratio naturalis historiae Plinii Secundi, with particular regard to Edward Bernard's catalogue and to the library of Queen Christina of Sweden. It also addresses the 'core of his library', finally sold by his daughter in 1752, and considers the biographical insights provided by the volumes in this collection, against the efforts Meibomius undertook to win renown as a scholar.